EFFORTS TO IMPROVE HR PERFORMANCE THROUGH TECHNOLOGY TRAINING IN THE PANDEMIC TIME COVID-19 - Sofyandi, Herman (CENTRAL ASIA AND THE CAUCASUS, 2022)
This research aims to identify how efforts to improve human resource performance through technology training during the COVID-19 pandemic. This research design uses multiple case studies to explore the use of networks that support the capabilities of small and medium enterprises (SMEs). Data analysis shows that with the support and technology training provided by SME owners to their employees, they get a number of benefits, including making SMEs able to compete and increasing sales sales, especially during the COVID-19 Pandemic. Therefore, this study suggests that SME managers should strive to provide training to their employees in the context of technology, especially digital marketing.